PERFORMANCE OF FOUR STRAINS OF BROILER CHICKEN GRANDPARENT STOCK FLOCK IN INDONESIA - Rofii, Rofii; Ulfah, Maria; Darwati, Sri; Muladno, Muladno (Fakultas Peternakan, Universitas Padjadjaran, 2023)
This study aims to compare the performance of broiler GPS flocks from 4 GPS strains in Indonesia (Cobb, Ross, Indian River, Hubbard). This research was conducted from November 2022 to March 2023. Data were collected from some breeding companies' audit results conducted by the Directorate General of Livestock and Animal Health. The results showed that the broiler GPS flock performance in the young age group showed a significance value of <0.05, and there was a significant difference in the HDP variable indicator. The average HDP weight for the Ross, Cobb, Indian River, and Hubbard GPS strains was 78.05±3.28, 74.00±3.30, 78.99±3.37 and 75.85±3.61, respectively. The average egg and hatchling weight was also significantly different among each strain, but only on the variable factor of the breeding company. There were no significant differences among the strain factor variables and primary product variables, such as the average number of DOC PS per hen by breeding company and strain. On average, a female GPS line in the young age group period for the Ross, Cobb, Indian River, and Hubbard strains produced 15.14 ± 2.2, 14.92 ± 4.6, 15.35 ±1.47, and 13.78 DOC, respectively. There is no mutual interaction between the performance of HDP flocks, egg weight, and hatching weight of DOC PS from variable factors of the breeding companies with each strain. Factorial interactions only occur in the primary product variable, meaning each broiler GPS strain reared by each breeder company in Indonesia has different performances.